2022
DOI: 10.3390/su14020820
|View full text |Cite
|
Sign up to set email alerts
|

Application of Corn Straw and Woody Peat to Improve the Absorption and Utilization of 15N-Urea by Maize

Abstract: Increasing nitrogen fertilizer use efficiency has become an environmental and economic demand in order to minimize losses of nitrogen and maximize the output from nitrogen added. The application of organic amendments with N fertilizers could be proposed as an important economic and environmental practice for improving N fertilizer use. A two-year field experiment was carried out using the 15N tracer technique to study the impact of corn straw and woody peat application on uptake and utilization of N fertilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Compared with CF treatment, PM increased the 2-yr mean value of NUE, NPFP, NUPE, NHI,NAP,and NAG by 0.04,4.01,5.86,3.04,6.03,and 7.35% compared with the CF treatment, reduced SNDR by 4.64%, the ST return did not improve N utilization. Pig manure treatment performance was the best among the three organic material followed by BR and ST. Lin et al (2022) also found that ST return increased the urea utilization rate by 18.62% because ST returning to the soil could promote urease activity, urea hydrolysis, and ammonium N accumulation, thus it could increase soil N availability and N supply capacity. And Meng et al (2021) also thought that ST retained an improved utilization rate of N fertilizer in the Loess Plateau of China.…”
Section: Relationships Between Organic Materials and N Utilizationmentioning
confidence: 85%
See 1 more Smart Citation
“…Compared with CF treatment, PM increased the 2-yr mean value of NUE, NPFP, NUPE, NHI,NAP,and NAG by 0.04,4.01,5.86,3.04,6.03,and 7.35% compared with the CF treatment, reduced SNDR by 4.64%, the ST return did not improve N utilization. Pig manure treatment performance was the best among the three organic material followed by BR and ST. Lin et al (2022) also found that ST return increased the urea utilization rate by 18.62% because ST returning to the soil could promote urease activity, urea hydrolysis, and ammonium N accumulation, thus it could increase soil N availability and N supply capacity. And Meng et al (2021) also thought that ST retained an improved utilization rate of N fertilizer in the Loess Plateau of China.…”
Section: Relationships Between Organic Materials and N Utilizationmentioning
confidence: 85%
“…Lin et al. (2022) also found that ST return increased the urea utilization rate by 18.62% because ST returning to the soil could promote urease activity, urea hydrolysis, and ammonium N accumulation, thus it could increase soil N availability and N supply capacity. And Meng et al.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, exploring fertilization measures that can improve soil fertility, increase yield and efficiency, and are environmentally friendly is of great significance for sustainable agricultural production in farmland. Due to organic manure now being available as an alternative nutrient resource, the utilization rate of chemical fertilizers is declining [9]. Therefore, how to optimize fertilization measures, to use organic manure instead of chemical fertilizer during the crop production, to improve the planting efficiency and make up for the gap in demand of oilseed flax, and to protect the farmland environment is an urgent problem that needs to be solved.…”
Section: Introductionmentioning
confidence: 99%